2005
DOI: 10.1598/jaal.49.3.4
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Queer‐Inclusive English Language Arts

Abstract: The authors argue for teaching queer‐inclusive English language arts (ELA). They report on a study that surveyed high school personnel across the United States, revealing that very few people in charge of ELA curricula value such inclusion. In response to these findings, the authors offer “images of the possible” in which texts and methods that could be used in queer‐inclusive ELA curricula are suggested. They advocate for teaching ELA that represents diverse people, including those who are lesbian, gay, bisex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(38 citation statements)
references
References 9 publications
(8 reference statements)
0
38
0
Order By: Relevance
“…The study found that the teachers tended to avoid issues related to sexual minorities, even when they were aware of the relevance of the topic to their students. This type of avoidance leads to classroom environments that are repressive and discriminatory toward LGBQ students and teaches heterosexual students to be intolerant and homophobic (Blackburn & Buckley, 2005;Khayatt, 1994). Because some of the teachers appeared to recognize the salience of LGBQ issues for the students, it is possible that relatively brief workshops might go a long way toward ameliorating the situation.…”
Section: Resultsmentioning
confidence: 99%
“…The study found that the teachers tended to avoid issues related to sexual minorities, even when they were aware of the relevance of the topic to their students. This type of avoidance leads to classroom environments that are repressive and discriminatory toward LGBQ students and teaches heterosexual students to be intolerant and homophobic (Blackburn & Buckley, 2005;Khayatt, 1994). Because some of the teachers appeared to recognize the salience of LGBQ issues for the students, it is possible that relatively brief workshops might go a long way toward ameliorating the situation.…”
Section: Resultsmentioning
confidence: 99%
“…We understand that, for many elementary school teachers, discussing topics of nonnormative gender in their classrooms feels awkward, sensitive, or difficult at best-if not morally wrong, unnecessary, or impossible (Blackburn & Buckley, 2005;Rands, 2009;Williams, 2002). As teachers and scholars who live gender in generally normative ways ourselves (sometimes called cisgender), we know it can be tempting to avoid those moments that challenge us and remind us we don't have all the answers, so as to enjoy the privilege our normative gender identities entail.…”
mentioning
confidence: 99%
“…Although we have suggested a queer critical approach to reading texts by critically analyzing the intersections of identity, including gender and sexuality, consideration of LGBTQ+‐inclusive texts is similarly important. Queer‐inclusive literature provides an opportunity for students to see themselves in stories (Blackburn & Buckley, ). Digital media sources such as video games, film trailers, blogs, and videos provide new ways to extend the limited selection of LGBTQ+ literature, which currently excludes less clearly defined sexualities, such as bisexual and transgender identities (DePalma, ).…”
Section: Resultsmentioning
confidence: 99%